Measuring Positive Psychosocial Sequelae in Patients with Advanced Cancer - Applebaum, Allison J. (Psychol Trauma, 2021)
OBJECTIVE: Posttraumatic growth and benefit finding describe the potential for positive changes resulting from traumatic experiences, including cancer. In oncology, these constructs are increasingly examined concurrently using the Post-Traumatic Growth Inventory (PTGI) and the Benefit Finding Scale (BFS). However, distinctions between these constructs, and their corresponding scales, are not altogether clear, and the burden of administering two lengthy questionnaires is evident, particularly for patients at end-of-life. METHOD: Baseline data from 209 participants enrolled in a randomized controlled trial evaluating the efficacy of a psychosocial intervention were analyzed. We assessed the structure and covariance of all PTGI and BFS items using item response theory to determine the extent to which these measures overlap and the potential value of their concurrent administration in patients with advanced cancer. RESULTS: Despite conceptual differences in posttraumatic growth and benefit finding, results indicated that these measures address the same underlying construct. We subsequently analyzed three abbreviated scales (7-,11-, and 16-items) that combine items from both scales to identify an optimal briefer combined scale. Results supported all three versions, with the 7- and 16-item measures appearing to have the best balance of content and concurrent validity, and the 11-item version optimizing information gained with brevity. CONCLUSIONS: These findings indicate that concurrent administration of the PTGI and BFS may be unnecessary given the high degree of overlap between these two measures, and that a brief subset of items may adequately evaluate positive change among patients with advanced cancer while reducing participant burden.